Optimization of Samapta Batang Police District Patrol to Prevent the Crime of Aggravated Theft - Ramadhani, Tasya Meldi (Advances in Police Science Research Journal, 2024)
The crime of aggravated theft has the highest crime rate in the Batang Police District jurisdiction. Batang Police through the Samapta Unit plays in preventing criminal cases, especially aggravated theft, by emphasizing prevention through patrolling activities. Routine patrols that is being carried out by the Samapta Unit are considered not optimal, becaused the number of crimes at the Batang Police District, especially the crime of aggravated theft. This study aims to identify and analyze the implementation and organizational resources of the Samapta Unit in Batang Police. This study uses a qualitative research Approach with a case study research to collect data by conducting interviews, observation and document studies. This study uses management theory, organizational resource theory and SWOT analysis theory as well as several concepts related to these problems, such the Patrol concept based on Perkabaharkam No 1 of 2017 concerning Patrols, the concept of aggravated theft, the concept of crime prevention, and the concept of optimization. The result from the research are that the Samapta patrol unit still has saveral deficiencies in the process of the planning, organizing, actuating and suppervising because it is not in accordance to the patrol SOP consisted in Peraturan Kepala Badan Pemeliharaan Keamanan Number 1 of 2017 abot Patrols. The resources for conducting patrols were not used optimally and there were factors that influenced the implementation of the Samapta Patrol of the Batang Police so that they could not be carried out optimally. What must be done by the Samapta Unit of the Batang Police is to make new breakthroughs and improve the quality of patrol personnel.